Impacts of decarbonization on the automotive after sales sector: A review of evidence. (May 2021) - Eslava-Bautista, Jorge; Cottrill, Caitlin D; Beecroft, Mark
Automotive after sales, which include provision of spare parts, customer service, and accessories sales, is one of the most profitable parts of the automotive industry and provides for an ongoing relationship with the customer. In times of recession, performance of after sales remains steady as it is highly independent of macroeconomic behaviors and keeps outstanding margins. Current automotive after sales are predominantly based on fossil fuel power train technologies, involving a significant number of replaceable working parts, lubricants, and supplies, and requiring ongoing manual labor. Current efforts to decarbonize the automotive industry, however, have the potential to disrupt this industry by shifting traditional after sales business models. The objective of this paper is to review the background and development of policies and actions in relation to the decarbonization of transport with a particular focus upon the role of the automotive after sales sector. The review considers the role of a range of stakeholders including multilateral bodies setting targets for participating nations; national governments; and the automotive industry, operating at varying scales. Electrification of vehicles and discouragement of car use and ownership are identified as key decarbonization strategies that could significantly impact upon car manufacturers and the broader automotive industry, which will in turn impact upon the after sales market. The review concludes that there has been limited research about impacts on after sales markets from transport decarbonization strategies. Areas of impact identified include reduction of working parts, fewer additional units, longer service intervals, changes in labor needs, disruption in customer retention, and changes to the repurchase cycle. In order to explore these potential impacts, the development of alternative future scenarios under different power train technologies and regional factors is recommended as an area for further research.